2017
DOI: 10.1002/hed.24838
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of epithelial-to-mesenchymal transition in laryngeal carcinoma: Its role in the different subsites

Abstract: The negative prognostic role of epithelial-to-mesenchymal transition has been confirmed and a predictive role in glottic tumors has been suggested, leading us to propose epithelial-to-mesenchymal transition as an additional adverse feature in laryngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The IHC evaluation for each antibody was performed by 2 experienced investigators who analyzed the immunostaining in the entire tumor area present in the slide (at magnification 20×). Results were expressed with a semiquantitative double score based on staining localization (nuclear or cytoplasmic) and intensity (negative, weak, moderate, strong) [31].…”
Section: Protein Expression Analysesmentioning
confidence: 99%
“…The IHC evaluation for each antibody was performed by 2 experienced investigators who analyzed the immunostaining in the entire tumor area present in the slide (at magnification 20×). Results were expressed with a semiquantitative double score based on staining localization (nuclear or cytoplasmic) and intensity (negative, weak, moderate, strong) [31].…”
Section: Protein Expression Analysesmentioning
confidence: 99%
“…Furthermore, E‐cadherin is also a key molecule involved in epithelial‐mesenchymal transition process, which is the hallmark for cancer metastasis. Researchers found that epithelial‐mesenchymal transition resulting from E‐cadherin loss contributed to invasion and metastasis of human tumors . The E‐cadherin loss with epithelial‐mesenchymal transition also promoted radioresistance in human tumor cells .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that epithelialmesenchymal transition resulting from E-cadherin loss contributed to invasion and metastasis of human tumors. [37][38][39] The E-cadherin loss with epithelial-mesenchymal transition F IGUR E 4 Sensitivity analysis for the pooled odds ratios with confidence interval (CIs) of the association between E-cadherin methylation and nasopharyngeal carcinoma risk. Results were computed by omitting each study in turn.…”
Section: Discussionmentioning
confidence: 99%
“…This transition is thought to be associated with cellular plasticity and loss of the epithelial adhesion marker, E-cadherin, and gain in expression of mesenchymal markers such as N-cadherin and vimentin [5,68]. These changes have been termed “cadherin switching” and have been associated with poor prognosis [4,7, 912]. EMT is also a characteristic of cancer initiating stem cells that may be responsible for tumor recurrence and treatment resistance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although EMT is a characteristic of increased motility and invasiveness, it remains unclear if EMT and tumor “stemness” are associated with the host immune response or immunosuppression in the tumor microenvironment [4,28,29]. The relationship of markers of EMT and potentially important prognostic factors such as pattern of invasion [3033] and tumor infiltrating lymphocytes [3438] remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%